The Terms of Concept and Its Interpretations in Linguistics - Marufjon Yuldashev; Shohkadam Haydarov (Researchparks Publishing, 2022)
This article provides information about the term of concept and its different interpretations in world linguistics, understanding of the term in conceptual research, the basic notions of the concept are more observable in linguocognitology and linguocultural studies, that the concept of linguoconcept is also a field of linguistics that should be studied on the basis of common criteria in interdisciplinary communication, linguoconcept is a concept and is considered to be a branch of the concept sphere to which it belongs.